1987
DOI: 10.1021/jo00230a028
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the syntheses of sesquiterpene lactones. 10. Improved syntheses of (+)-tuberiferin and the related .alpha.-methylene-.gamma.-lactones and their biological activities

Abstract: Supplementary Material Available; Reaction rates for acid-promoted transformations under heating are summarized in Figures 1-3 (4 pages). Ordering information is given on any current masthead page.Studies on the Syntheses of Sesquiterpene Lactones. 10.1 2Improved Syntheses of (+ )-Tuberiferin and the Related «-Methylene 7-Lactones and Their Biological Activities

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 0 publications
2
27
0
Order By: Relevance
“…The 13 C-NMR spectrum exhibited downfield-shifted signals at d C 204.7 (8a) and 202.6 (7a), assignable to C(3) and indicating a CO moiety in that position. Signals of the main component (7a) were in perfect agreement with those reported for tuberiferin [12]. 1 H-NMR data of the second component (8a) were similar to those reported for 7a, differing mainly in an additional signal at d H 3.75 (s, 3 H), assignable to a MeO group.…”
supporting
confidence: 85%
“…The 13 C-NMR spectrum exhibited downfield-shifted signals at d C 204.7 (8a) and 202.6 (7a), assignable to C(3) and indicating a CO moiety in that position. Signals of the main component (7a) were in perfect agreement with those reported for tuberiferin [12]. 1 H-NMR data of the second component (8a) were similar to those reported for 7a, differing mainly in an additional signal at d H 3.75 (s, 3 H), assignable to a MeO group.…”
supporting
confidence: 85%
“…A large number of pseudoguaianolides, 4,5-secopseudoguaianolides, guaianolides, and 4,5-secoguaianolides have been shown to exhibit biological activities, including antitumoral [23], root-growth and germination inhibitory activities [24][25][26][27], as well as preventive or curative activities against phytopatogenic fungi [24,26]. Shimoma et al [28] reported the regio-and stereoselective synthesis of common synthetic intermediates via kinetic resolution with Lipase PS, (Fig.…”
Section: Herbicidesmentioning
confidence: 99%
“…Thus, Pitacco et al [84] explored the possibility of using enzymes for the kinetic resolution of an α-methylene-γ-lactone, ethyl 2-methyl-4-methylene tetrahydro-5-oxo-2-furancarboxylate (27). The resolution was achieved with Porcine pancreatic lipase (PPL) and Candida rugosa lipase (CRL) in the presence of a cosolvent, and afforded both enantiomers of the corresponding acid with high enantiomeric excesses, (Fig (11)).…”
Section: 3) Of Candidamentioning
confidence: 99%
“…1A, were synthesized according to the procedure previously described (16,17). In brief, (11S)-3-oxoeudesmano-13,6␣-lactone derivative, which exists in the form of needles (m.p.…”
mentioning
confidence: 99%